THE CROSSROADS BETWEEN ACTORS, NORMS, PRACTICES AND INSTITUTIONS: MASS MIGRATION FROM VENEZUELA IN SOUTH AMERICA - Aguilar, Sérgio (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
Intergovernmental organisations and institutions are generally created to discuss and find collective solutions to problems that transcend national borders and individual states’ capacities. However, certain crises push for isolated, typically restrictive, actions from governments, making the role of such institutions somewhat murky. The South American Conference on Migration (SCM), the Specialized Migration Forum of the Southern Common Market (Mercosur), and the Andean Committee of Migration Authorities of the Andean Community of Nations (CAN) are three intergovernmental forums that were created with the aim of negotiating agreements, creating and implementing community legislation, and achieving regional policy with regards to migration. However, from 2015, mass migration from Venezuela, which was considered a crisis by South American governments, led to restrictive policies in some countries. In this context, this paper discusses the linkages between institutions, actors, norms and practices by examining the interactions between SCM, Mercosur and CAN and the practices of Brazil, Colombia, Ecuador and Peru regarding the Venezuelan migration crisis. Through a qualitative approach, observations of practice and discourse, and the critical analysis thereof, this paper discusses debates and decisions within institutions; the emergence and non-compliance of collective norms; and the contradictory practices employed as responses to the migration crisis.